Impact of Intra-Organizational Environmental Characteristics on Entrepreneurial Marketing Intensity and Performance in the Family Business - Aqwila, Daniella Claudia; Herdinata, Christian; Dewi, Liliana (PT. Riset Press International, 2026)
Family businesses constitute a dominant force in emerging economies, yet many struggle to sustain competitiveness due to limitations in adaptive marketing capabilities and internal organizational alignment. While entrepreneurial marketing (EM) has been widely recognized as a strategic response to dynamic and uncertain environments, empirical understanding of how intra-organizational factors shape its intensity and outcomes, particularly within family firms, remains limited. Addressing this gap, this study develops and empirically tests a model linking intra-organizational environmental characteristics to entrepreneurial marketing intensity (EMI), and subsequently to organizational performance and competitive advantage in family businesses. Drawing on a quantitative research design, data were collected from 231 Indonesian family firms operating for at least three years and affiliated with the Ciputra University Family Business community. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), this study examines the effects of cooperative competency, governance and administrative mechanisms, institutional support, planning flexibility, planning horizon, and locus of planning on EMI. The results reveal that cooperative competency, deep locus of planning, governance and administrative mechanisms, and institutional support exert strong and significant positive effects on EMI. In contrast, planning flexibility and planning horizon do not significantly enhance EMI, suggesting that excessive emphasis on flexibility or long-term planning may constrain entrepreneurial responsiveness in family firms. Furthermore, EMI demonstrates a robust and positive impact on both organizational performance and competitive advantage. This study advances the entrepreneurial marketing literature by offering a nuanced, context-specific explanation of how internal organizational conditions enable or inhibit marketing-driven entrepreneurship in family businesses. The findings challenge conventional assumptions regarding planning flexibility and extend EM theory beyond its traditional focus on SMEs by emphasizing the unique structural and cultural dynamics of family firms. Practically, the study provides actionable insights for family business leaders to strengthen internal coordination, governance, and institutional alignment in order to leverage EMI as a strategic driver of sustained performance and competitive positioning in volatile markets.